Tingkat Kebugaran Jasmani Siswa Kelas X Di Sekolah Menengah Atas Negeri 2 Kota Pasuruan - Putri, Fildzah Machdi; Kurniawan, Ari Wibowo (Jurnal Master Penjas & Olahraga, 2023)
This research was motivated by the lack of data on the physical fitness of class X students at State Senior High School 2 Pasuruan City. Data collection techniques used measurement techniques in the form of tests, namely the 60 m running speed test, the 1200 m running endurance test for men and the 1000 m running test for women, the hanging arm muscle endurance test for lifting the body for men and hanging elbows for women, endurance tests abdominal muscles sit up 60 seconds, and vertical jump leg muscle explosive power test. Based on the results of the research that has been presented, it can be concluded that the physical fitness level of students at SMA Negeri 2 Pasuruan City is mostly in the moderate category with a percentage of 71% for boys and the majority in the good category with a percentage of 80% for girls.